What do we expect from an ombudsman? Narratives of everyday engagement with the informal justice system in Germany and the UK. Issue 4 (9th November 2016) - Creutzfeldt, Naomi
Abstract: This paper looks at expectations people have of informal justice mechanisms through a rich empirical dataset of 2, 775 recent ombudsman users in Germany and the UK. In a cross-cultural comparison, the ombudsman as a model of justice is explored. Not much is known about people's expectations of the ombudsman model; this paper starts to fill the gap. Four roles became apparent in cross-cultural narratives in the dataset: people who interact with ombudsmen expect them to be interpreters, advocates, allies and instruments. The identified roles are largely common to both countries, but in some aspects they show national specificities. These national specificities are seen mainly in the use of language; in Germany, it is more legalistic in comparison to the UK. I argue that this might be related to what has been described as the general legal culture of each country and the institutional set-up.